2013
DOI: 10.1111/eje.12049
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for a problem‐oriented pharmacobiochemistry course in dental education

Abstract: Problem-oriented learning is an effective method of learning that increases students' learning motivation, improves the relationship amongst students and results in open-minded discussions. In this study, a new problem-oriented pharmacobiochemistry course related to 'oxidative metabolism of drugs by cytochrome P450 (CYP450) systems' was designed. Students were divided into seven groups. Three keywords related to drug interaction through CYP450 were provided to each group in order for them to conduct research o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…A recent study reported that students who enrolled in a PBL-based curriculum performed significantly better than students who enrolled in a traditional lecture-based curriculum 34. Similar findings were also reported in other studies 35–37. Our study showed that the Internet was the most used learning resource during SDL to prepare for PBL sessions.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study reported that students who enrolled in a PBL-based curriculum performed significantly better than students who enrolled in a traditional lecture-based curriculum 34. Similar findings were also reported in other studies 35–37. Our study showed that the Internet was the most used learning resource during SDL to prepare for PBL sessions.…”
Section: Discussionsupporting
confidence: 89%
“…[24] Similar finding was also reported in other studies. [112526] Comparison of the students’ responses according to the academic year showed significant differences among different academic years (students assume responsibility for their own learning; P = 0.037). Among all academic years, first-year students reported a higher percentage for self-learning (72%), which is probably due to the fact that these students are not yet used to seek help from other or they may not know from where they can get support during or after PBL sessions.…”
Section: Discussionmentioning
confidence: 99%
“…9 In our study, students had settled the memory of sub jects of sterilization-disinfection and disease processes because these are highlighted many times in various clinical courses. 10 Henzi et al 3 performed a SWOT analysis (strengths, weaknesses, opportunities, and threats) of the dental curriculum, and "education based on memorization" was found as a weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we observed that the success rate of students who attended a problemoriented course was higher than when the same students attended a lecturebased course only. 10 In this type of learning method, the information given to solve the problem cases is more memorable, and the courses are designed to provide stu dents with clinical competency development to manage the health of patients in terms of dentistryrelated illness. Selfdirected learning and communication skills contribute to several of the supporting compe tences adopted by the ADEE.…”
Section: Discussionmentioning
confidence: 99%